STUDI PENGOLAHAN SOSIS IKAN KERANDANG (Channa pleurophthalma) DENGAN BAHAN PENGISI KACANG MERAH (Phaseolus vulgaris L) - Restu Restu (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study is a diversified processing of fish. The aims of the experiment completely randomized design to study the effect of red bean paste in the processing of fish sausage kerandang (Channa pleurophthalma). Results showed that the addition of red bean paste on the flesh of the fish kerandang very significant effect. The Best fish sausage obtained C treatment, namely by mixing fish meat kerandang creamed 500 grams with 300 grams of red bean paste. Criteria nutritions value generated as follows: protein = 16.45%; Carbohydrates = 24.32%; Fat = 1.07%; water = 58.53%; the average value of organoleptic = 7.41 on hedonic scale. Specifications sausage produced is clean and attractive, distinctive smell of sausage and appealing taste, peculiar taste of fish sausage and tasty, with a texture quite compact.